Maté consumption association with upper aerodigestive tract cancers: A systematic review and meta-analysis. (July 2018) - Mello, Fernanda Weber; Scotti, Fernanda Marcello; Melo, Gilberto; Warnakulasuriya, Saman; Guerra, Eliete Neves Silva; Rivero, Elena Riet Correa
Highlights: Maté increased the overall odds for upper aerodigestive tract cancers. Consumption at both low and high temperatures increased the odds for these cancers. Both low and high volume of maté intake increased the odds for these cancers. An intake of more than one liter of maté per day had significantly higher odds. Abstract: Maté is a beverage regularly consumed by Latin American populations. Upper aerodigestive tract (UADT) cancers are frequent in this region and are suspected to be associated with maté consumption. The aim of this systematic review and meta-analysis was to answer a focused question: "Is there an association between maté consumption and occurrence of the UADT cancer?". Studies investigating any association between maté consumption and occurrence of UADT cancer were included. Out of the 569 studies, 18 met the inclusion criteria for qualitative and 15 for quantitative analysis. An increased odds was observed regarding maté consumption and overall occurrence of UADT cancer (OR = 2.24; 95%CI = 1.74–2.87). Consistent evidence of a positive association was found for all UADT subsites, oral, pharynx, esophagus and larynx. No differences in effect were found between consumption of cold/warm and hot/very hot mate (OR = 1.08; 95%CI = 0.83–1.41). Consumption of more than one liter of maté per day was associated with increased odds of having UADT cancer compared to an intake of less than one liter per day (OR = 1.72; 95%CI = 1.47–2.01). According to published data, regardless of the temperature, maté consumption significantly increased the odds of occurrence of UADT cancer.